1975
DOI: 10.1139/m75-015
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of a peroxidogenic strain of Streptococcus mitior (mitis)

Abstract: An antibacterial substance produced by a strain of Streptococcus mitior, and isolated from a human throat culture, was found to inhibit the growth of streptococci and staphylococci. The substance was characterized as hydrogen peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The mechanisms of interference mediated by oral bacteria in this report are not clear, although many investigators have reported that viridans group streptococci produce substances with bacteriocin-like activity, including H 2 O 2 [7,11,[29][30][31]. In the accompanying article [32], we report the results of our investigation of the role of H 2 O 2 in preventing MRSA colonization of oral cavities in newborns.…”
Section: Discussionmentioning
confidence: 84%
“…The mechanisms of interference mediated by oral bacteria in this report are not clear, although many investigators have reported that viridans group streptococci produce substances with bacteriocin-like activity, including H 2 O 2 [7,11,[29][30][31]. In the accompanying article [32], we report the results of our investigation of the role of H 2 O 2 in preventing MRSA colonization of oral cavities in newborns.…”
Section: Discussionmentioning
confidence: 84%
“…Streptococci possess superoxide dismutase, and many strains are known to produce H # O # . There have been many studies on H # O # production by oral streptococci (Garcia-Mendoza et al, 1993 ;Holmberg & Hallander, 1973 ;LeBien & Bromel, 1975 ;Liebana et al, 1993 ;Willcox & Drucker, 1988), and this characteristic has often been important for the classification of these species (McLeod & Gordon, 1922 ;Whiley et al, 1990). However, there are few reports on H # O # production by S. pyogenes (Gibson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory substances produced by our isolates have not been identified, but probably do not include hydrogen peroxide, since the strains were all grown anaerobically (LeBien and Bromel, 1975;Malke et al, 1974). Since L. mtrinus isolates produce large amounts of lactic acid , it would be reasonable to assume that this product accounts, at least in part, for inhibitory activities recorded with this species.…”
Section: Discussionmentioning
confidence: 97%